Lipids at the Crossroad of α-Synuclein Function and Dysfunction: Biological and Pathological Implications - Alza, Natalia P.; Iglesias González, Pablo A.; Conde, Melisa A.; Uranga, Romina M.; Salvador, Gabriela A. (Frontiers in Cellular Neuroscience, 2019)
Since its discovery, the study of the biological role of α-synuclein and its pathological implications has been the subject of increasing interest. The propensity to adopt different conformational states governing its aggregation and fibrillation makes this small 14-kDa cytosolic protein one of the main etiologic factors associated with degenerative disorders known as synucleinopathies. The structure, function, and toxicity of α-synuclein and the possibility of different therapeutic approaches to target the protein have been extensively investigated and reviewed. One intriguing characteristic of α-synuclein is the different ways in which it interacts with lipids. Though in-depth studies have been carried out in this field, the information they have produced is puzzling and the precise role of lipids in α-synuclein biology and pathology and vice versa is still largely unknown. Here we provide an overview and discussion of the main findings relating to α-synuclein/lipid interaction and its involvement in the modulation of lipid metabolism and signaling.